1976
DOI: 10.1111/j.1651-2227.1976.tb04907.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Studies in Children Before and After Splenectomy

Abstract: Fourteen children underwent splenectomy for congenital spherocytosis, splenomegaly, or thrombocytopenia. The patients were studied twice before the operation, three times during the first postoperative month, and one year later. A transitory rise in neutrophils and serum IgA was seen postoperatively; there was a modest but long-lasting increase in lymphocytes and a marked elevation of eosinophils. An immediate decline in serum IgM concentration was observed only in patients with an uncomplicated postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
2

Year Published

1977
1977
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 11 publications
2
7
0
2
Order By: Relevance
“…These results show that the number of lymphocytes was increased in S C A and in splenectomized subjects as have been previously reported [15,16,[24][25][26][27][28][29][30]], This increment is more pronounced in S C A and the inter pretation for this finding is unclear. Differences be tween the effect of autosplenectomy and surgical splenectomy and the influence of previous transfu sions should be considered.…”
Section: Discussionsupporting
confidence: 35%
“…These results show that the number of lymphocytes was increased in S C A and in splenectomized subjects as have been previously reported [15,16,[24][25][26][27][28][29][30]], This increment is more pronounced in S C A and the inter pretation for this finding is unclear. Differences be tween the effect of autosplenectomy and surgical splenectomy and the influence of previous transfu sions should be considered.…”
Section: Discussionsupporting
confidence: 35%
“…Our result was also demonstrated that alloantibodies-formation was higher in splenectomised subjects and associated with splenectomy. Several studies have shown that splenectomy is associated with changes in both humoral and cell mediated immunity, including decreased serum IgM concentrations and raised serum IgG and IgA concentrations [19][20][21][22]. Thromboembolic events and hypercoagulable state have been reported in b-TM patients and more frequent in splenectomized patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of cell-mediated immunity after splenec tomy has been suggested, the herpes simplex virus-in duced lymphocyte transformation being reduced [16]. In contrast, phytohemagglutinin-induced lymphocyte transformation is unchanged [16] or only depressed during the immediate postoperative period [1,2].…”
Section: Introductionmentioning
confidence: 99%